1993
DOI: 10.1002/pro.5560021115
|View full text |Cite
|
Sign up to set email alerts
|

A 19F‐NMR study of the membrane‐binding region of D‐lactate dehydrogenase of escherichia coli

Abstract: D-Lactate dehydrogenase (D-LDH) is a membrane-associated respiratory enzyme of Escherichia coli.The protein is composed of 571 amino acid residues with a flavin adenine dinucleotide (FAD) cofactor, has a molecular weight of approximately 65,000, and requires lipids or detergents for full activity. We used NMR spectroscopy to investigate the structure of D-LDH and its interaction with phospholipids. We incorporated 5-fluorotryptophan (SF-Trp) into the native enzyme, which contains five tryptophan residues, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Furthermore, residues 280 and 309 are within 15-20 Å of the membrane, which is in the range of the effect of nitroxide-spin-label on the 19 F resonance. Residue 279, postulated (13) to be close to the lipid phase, belongs to the cap domain, and, in the model below, is close to the membrane.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, residues 280 and 309 are within 15-20 Å of the membrane, which is in the range of the effect of nitroxide-spin-label on the 19 F resonance. Residue 279, postulated (13) to be close to the lipid phase, belongs to the cap domain, and, in the model below, is close to the membrane.…”
Section: Discussionmentioning
confidence: 95%
“…4. Previous studies (12)(13)(14)(15) have shown that residues Phe-339, Phe-340, Phe-341, Phe-356, Phe-357, and Phe-361, among others, are likely to be close to the lipid phase. These residues are part of the modeled region and lie within 7-12 Å of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…D-Lactate dehydrogenase interacts with the cytoplasmic membrane and requires detergent for solubilization, yet has no lengthy stretches of hydrophobic amino acids. It apparently interacts with the membrane via several separated structural elements (Sun et al 1993). We now show that the GlpAC dimer transfers its reducing equivalents to the terminal reductase via GlpB, perhaps in a manner analogous to proline dehydrogenase, although we have not been able to distinguish a difference in binding associated with redox state (M.E.R.…”
Section: Field Intensity (Gauss) Field Intensity (Gauss)mentioning
confidence: 92%
“…Although there are examples of incorporation of fluorinated aliphatic amino acids,6 most fluorine atoms are incorporated into proteins as part of the aromatic side‐chains Tyr (typically as 3‐fluoro‐Tyr), Trp (4‐, 5‐, or 6‐fluoro‐Trp),7, 8 or Phe (2‐, 3‐, or 4‐fluoro‐Phe) 9. Introduction of fluorine into aromatic rings represents a very small overall change in amino acid side‐chain volume, which is quite conservative compared with typical substitutions introduced by mutagenesis 4…”
Section: Introductionmentioning
confidence: 99%
“…However, given that aromatic residues are often involved in complex interactions both in the interior of the protein and at the surface, differential effects of incorporating various fluorinated isomers at locations removed from enzyme active sites are possible. In spite of this, only a few studies involving isomeric fluorine incorporation have been reported,8, 11 and fewer still that compare the effects of these modifications on activity and conformation 9…”
Section: Introductionmentioning
confidence: 99%